Genetic Polymorphisms and Adverse Events on Unbound Imatinib and Its Active Metabolite Concentration in Patients With Gastrointestinal Stromal Tumors - Qian, Yi; Sun, Lu-Ning; Liu, Yang-Jie; Zhang, Qiang; Xu, Jiang-Hao; Ma, Zeng-Qing; Zhang, Xue-Hui; Xu, Hao; Wang, Yong-Qing (Frontiers in Pharmacology, 2019)
Imatnib is a first-line drug for the treatment of gastrointestinal stromal tumours (GIST). This study aims to investigate the influence of different kinds of protein concentrations and genetic polymorphisms of metabolizing enzymes and drug transporters on unbound imatinib and its active metabolite N-desmethyl-imatinib concentration, as well as the relationship between adverse drug reactions (ADRs) and drug concentration. A total of 62 Chinese patients with GIST were genotyped for five single nucleotide polymorphisms (SNPs). Total and unbound 3h and trough concentration of imatinib and N-desmethyl-imatinib in GIST patients were determinated by a LC-MS/MS method combined with an equilibrium dialysis. Single-Use Red Plate with inserts was used to separate the unbound drug. When the protein concentration became higher, the unbound imatinib and N-desmethyl-imatinib plasma concentration got higher (P<0.05). Patients with GA genotype in rs755828176 had significantly higher unbound N-desmethyl-imatinib dose-adjusted trough plasma concentrations (p=0.012). Patients with CC genotype in rs3814055 had significantly higher unbound imatinib dose-adjusted trough plasma concentrations (p=0.040). The mean total imatinib C3h of patients with ADRs (3.10±0.96 µg/mL) was significantly higher than that of patients without ADRs (p=0.023). The mean total N-desmethyl-imatinib C3h of patients (0.64±0.21µg/mL) with ADRs was significantly higher than that of patients without ADRs (p=0.004). The mean unbound N-desmethyl-imatinib C3h of patients with ADRs (6.49±2.53 ng/mL) was significantly higher than that of patients without ADRs (p=0.042). The total and unbound C3h of imatinib and N-desmethyl-imatinib in patients with ADRs was significantly higher than that in patients without ADRs (p<0.05). Protein concentrations have great influence on the unbound imatinib and N-desmethyl-imatinib concentrations. The genetic polymorphisms of CYP3A4 rs755828176 and NR1I2 rs3814055 were significantly associated with unbound imatinib and N-desmethyl-imatinib dose-adjusted trough plasma levels. The total and unbound imatinib or N-desmethyl-imatinib concentration in patients with GIST was also significantly correlates with ADRs.